2017
DOI: 10.1007/s13300-017-0248-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Increases in Morning Spot Urinary Glucose Excretion and Decreases in HbA1C in Patients with Type 2 Diabetes After Taking an SGLT2 Inhibitor: A Retrospective, Longitudinal Study

Abstract: Introduction Sodium glucose co-transporter 2 (SGLT2) inhibitors increase urinary glucose excretion (UGE) by reducing the renal threshold for glucose excretion, which results in decreased serum glucose concentrations in patients with type 2 diabetes mellitus (T2D). However, no study to date has determined whether larger increases in UGE after SGLT2 inhibitor treatment correspond to larger reductions in glycated hemoglobin (HbA1C).MethodsWe enrolled participants who were newly prescribed an SGLT2 inhibitor (dapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…We also demonstrate that while urinary glucose excretion is a direct measure of SGLT inhibitor action, FGE did not improve prediction of ΔHbA1c in this study. This finding accords with that of a retrospective Korean study that found no association between urine glucose/creatinine ratio and ΔHbA1c 12 weeks after starting either dapagliflozin or ipragliflozin 18 . It is possible that changes in medication, diet and exercise during the study hampered our ability to identify a relationship between glycosuria and ΔHbA1c.…”
Section: Discussionsupporting
confidence: 89%
“…We also demonstrate that while urinary glucose excretion is a direct measure of SGLT inhibitor action, FGE did not improve prediction of ΔHbA1c in this study. This finding accords with that of a retrospective Korean study that found no association between urine glucose/creatinine ratio and ΔHbA1c 12 weeks after starting either dapagliflozin or ipragliflozin 18 . It is possible that changes in medication, diet and exercise during the study hampered our ability to identify a relationship between glycosuria and ΔHbA1c.…”
Section: Discussionsupporting
confidence: 89%
“…We initially used ΔUGE as a PD biomarker because of its mechanism of action and we found that the maximum effect and affinity on UGE was significantly different between different SGLT2 inhibitors and between patients and healthy subjects. It was consistent with one paper which even concluded that the ΔUGE has no relationship with FPG or HbA1c, which impeded the achievement of our preset aims 27 . Therefore, we proposed a better mechanistic PD biomarker to construct this system‐dependent model.…”
Section: Discussionsupporting
confidence: 85%
“…In a Japanese clinical trial, the young age group (≤ 40 years) showed a better effectiveness in glycemic control with a larger increase in urine glucose excretion [ 16 ]. However, another study reported that a larger urinary glucose excretion did not reflect a better HbA1c reduction [ 18 ]. As expected, these results suggest that the insulin-independent mechanism for the glucose-lowering effect of an SGLT2 inhibitor is not simple.…”
Section: Discussionmentioning
confidence: 99%